On the tip of a wave : how Ai Weiwei's art is changing the tide - Ho, Joanna (Orchard Books/Scholastic Inc., 2023)
"From the New York Times bestselling author of Eyes that Kiss in the Corners and Eyes that Speak to the Stars, comes a moving text about the life and work of social activist and artist, Ai Weiwei. Told in Joanna Ho's lyrical writing, this is the story behind Ai Weiwei's Lifejackets exhibit at Konzerthaus Berlin. As conditions for refugees got worse, Ai Weiwei was inspired by the discarded lifejackets on the shores of Lesbos to create a bold installation that would grab the attention of the world. With Catia Chien's dynamic and stunning illustrations, we see how Ai Weiwei became the activist and artist he is today while proving the power of art within humanity"--